Formation and Redox Interconversion of Niobium Methylidene and Methylidyne Complexes. (25th April 2016) - Searles, Keith; Smith, Kyle T.; Kurogi, Takashi; Chen, Chun‐Hsing; Carroll, Patrick J.; Mindiola, Daniel J.
Abstract: The niobium methylidene [{(Ar′O)2 Nb}2 (μ2 ‐Cl)2 (μ2 ‐CH2 )] (2 ) can be cleanly prepared via thermolysis or photolysis of [(Ar′O)2 Nb(CH3 )2 Cl] (1 ) (OAr′=2, 6‐bis(diphenylmethyl)‐4‐tert‐butylphenoxide). Reduction of2 with two equivalents of KC8 results in formation of the first niobium methylidyne [K][{(Ar′O)2 Nb}2 (μ2 ‐CH)(μ2 ‐H)(μ2 ‐Cl)] (3 ) via a binuclear α‐hydrogen elimination. Oxidation of3 with two equiv of ClCPh3 reforms2 . In addition to solid state X‐ray analysis, all these complexes were elucidated via multinuclear NMR experiments and isotopic labelling studies, including a crossover experiment, support the notion for a radical mechanism as well as a binuclear α‐hydrogen abstraction pathway being operative in the formation of2 from1 .